Exploring pre-exposure prophylaxis (PrEP) modality preferences among black cisgender women attending family planning clinics in Chicago via a cross-sectional mixed-methods study - Sadia Haider; Amy K Johnson; Emily Ott; Eleanor E Friedman; Agustina Pandiani; Amy Moore; Isa Alvarez; Catherine Desmarais (BMJ Public Health)
Background Despite pre-exposure prophylaxis (PrEP) demonstrated effectiveness, black cisgender women continue to be at an elevated risk for HIV acquisition and uptake of daily oral PrEP is low in this population in the USA. As advancements in PrEP delivery options continue, it is important to understand women’s acceptability of these additional options, specifically black cisgender women, in order to inform uptake and adherence among this population at increased need of HIV prevention options.Setting A cross-sectional survey among black cisgender women ages 13–45 (inclusive) attending women’s health clinics in Chicago, Illinois, USA, prior to the approval of cabotegravir long-acting injectable.Methods Descriptive statistics were used to describe the sample and bivariate analysis was used to detect differences between categorical and outcome variables using χ2 test. Responses to open-ended questions were thematically coded to explore black cisgender women’s attitudes and preferences between the three methods of PrEP delivery including vaginal ring, long-acting injectable and a combined method that would prevent both pregnancy and HIV.Results In total, 211 cisgender women and adolescents responded to the survey. Both injections and combination pills were popular among participants, with 64.5% and 67.3% expressing interest in these forms of PrEP, respectively. The least popular method was the vaginal ring option, with 75.4% of respondents indicating that they would not consider using this modality. Overall, responses were not statistically different between the two surveys administered (χ2 p values for injection PrEP method 0.66, combination PrEP method 0.93 and ring PrEP method 0.66) suggesting that the popularity of each method was not dependent on clinic location or the age of participants.Conclusion This research provides important insights into the preferences and attitudes of different PrEP modalities among black cisgender women. As different modalities continue to be approved for use among cisgender women, more research is needed to investigate the acceptability and preferences of these different modalities in order to improve uptake and adherence among this population.